Beispiel Nr: 22
$ \text{Gegeben:} \\ a1 \cdot x +b1 \cdot y =c1\\ a2 \cdot x +b2 \cdot y =c2 \\ \\ \text{Gesucht:} \\\text{x und y} \\ \\ \textbf{Gegeben:} \\ \\ -7 x +9 y =-3\\ 5 x -6 y = -4 \\ \\ \\ \\ \textbf{Rechnung:} \\\begin{array}{l|l} \begin{array}{l} \\I \qquad -7 x +9 y =-3\\ II \qquad 5 x -6 y = -4 \\ I \qquad -7 x +9 y =-3 \qquad / \cdot5\\ II \qquad 5 x -6 y = -4 \qquad / \cdot7\\ I \qquad -35 x +45 y =-15\\ II \qquad 35 x -42 y = -28 \\ \text{I + II}\\ I \qquad -35 x +35 x+45 y -42 y =-15 -28\\ 3 y = -43 \qquad /:3 \\ y = \frac{-43}{3} \\ y=-14\frac{1}{3} \\ \text{y in I}\\ I \qquad -7 x +9\cdot \left(-14\frac{1}{3}\right) =-3 \\ -7 x -129 =-3 \qquad / +129 \\ -7 x =-3 +129 \\ -7 x =126 \qquad / :\left(-7\right) \\ x = \frac{126}{-7} \\ x=-18 \\ L=\{-18/-14\frac{1}{3}\} \end{array} & \begin{array}{l} \\I \qquad -7 x +9 y =-3\\ II \qquad 5 x -6 y = -4 \\ I \qquad -7 x +9 y =-3 \qquad / \cdot\left(-2\right)\\ II \qquad 5 x -6 y = -4 \qquad / \cdot\left(-3\right)\\ I \qquad 14 x -18 y =6\\ II \qquad -15 x +18 y = 12 \\ \text{I + II}\\ I \qquad 14 x -15 x-18 y +18 y =6 +12\\ -1 x = 18 \qquad /:\left(-1\right) \\ x = \frac{18}{-1} \\ x=-18 \\ \text{x in I}\\ I \qquad -7 \cdot \left(-18\right) +9y =-3 \\ 9 y +126 =-3 \qquad / -126 \\ 9 y =-3 -126 \\ 9 y =-129 \qquad / :9 \\ y = \frac{-129}{9} \\ y=-14\frac{1}{3} \\ L=\{-18/-14\frac{1}{3}\} \end{array} \end{array} $